2004
DOI: 10.2166/wst.2004.0739
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting nitrogen removal by nitritation/denitritation

Abstract: Nitrogen removal from wastewater with high nitrogen concentration and low COD/N ratio via nitrite is advantageous. The specific character of the sludge liquor enables the application of such a method. The factors affecting process efficiency were studied. From the factors followed pH, NH4+/NH3 and NO2-/HNO2 concentration and distribution seem to be most important, using sequencing batch reactor technology and treating wastewater with high NH4+ concentration (above 1 g/l). The efficient oxidation of N-NH4+ to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 0 publications
2
31
0
8
Order By: Relevance
“…Contrary to these findings, our research showed that, even with free ammonia concentrations equal to 17.3 mg NH 3 .L -1 (maximum value during the whole study), no imbalance was observed during nitritation. These results are in agreement with Jenicek et al (2004), who successfully removed ammonia via nitrite even at free ammonia concentrations varying from 14.0 to 32.0 mg NH 3 .L -1 . Although other researchers (Phillips et al, 2002;Fux e Siegrist, 2004;Jenicek et al, 2004) concluded that the maintenance of sustained NO 2 --N accumulation in biological activated sludge systems depends on the adoption of high temperatures (theoretically, the specific growth rate of NOB decreases above 35 o C), we found that, even when the SBR operated at temperatures that are considered favorable to nitrite oxidizers (T < 25ºC), the presence of nitrate was not observed.…”
Section: Conditions For Nitrite Predominancesupporting
confidence: 92%
“…Contrary to these findings, our research showed that, even with free ammonia concentrations equal to 17.3 mg NH 3 .L -1 (maximum value during the whole study), no imbalance was observed during nitritation. These results are in agreement with Jenicek et al (2004), who successfully removed ammonia via nitrite even at free ammonia concentrations varying from 14.0 to 32.0 mg NH 3 .L -1 . Although other researchers (Phillips et al, 2002;Fux e Siegrist, 2004;Jenicek et al, 2004) concluded that the maintenance of sustained NO 2 --N accumulation in biological activated sludge systems depends on the adoption of high temperatures (theoretically, the specific growth rate of NOB decreases above 35 o C), we found that, even when the SBR operated at temperatures that are considered favorable to nitrite oxidizers (T < 25ºC), the presence of nitrate was not observed.…”
Section: Conditions For Nitrite Predominancesupporting
confidence: 92%
“…In one particular study realized [13,14,15], it was found that in order to remove nitrogen total-NT and phosphorus total-PT the wastewater keeps the optimal OD at 3 mg/L, getting a performance of 88.4% for NT and 89.5 % for PT.…”
Section: Imentioning
confidence: 99%
“…(Liu, 2000). The efficiency of the nitrification process depends on the specific velocity of nitrification (Henze, 2002), which in turn is established by the following factors: a) dissolved oxygen, b) temperature, c) pH (adequate between 7.2 and 8.5), d) the ratio DBO 5 /NTK, and e) the presence of inhibitor and toxic substances (Droste, 1997;Metcalf & Eddy, 2003;Lee, 2002;Randall, 1992;Holakoo, 2005;Jenicek, 2004 andKeller, 2001). The kinetic expressions involved in this stage are given by the equation that interrelates cell growth and the elimination of ammonium, in function of the growth of autotroph organisms through the Monod equation (Gil, 1998;Ferrer, 2008;Metcalf & Eddy, 2003;Crites, 2000;Orozco, 2005 andEPA, 1975), both in the nitrosomonas phase and in the nitrobacter, as follows.…”
Section: Biological Kinetics For the Removal Of Nitrogenmentioning
confidence: 99%